Osteology of Pseudochampsa ischigualastensis gen. et comb. nov. (Archosauriformes: Proterochampsidae) from the Early Late Triassic Ischigualasto Formation of Northwestern Argentina - Trotteyn, Maria Jimena (2014)
Proterochampsids are crocodile-like, probably semi-aquatic, quadrupedal archosauriforms characterized by an elongated and dorsoventrally low skull. The group is endemic from the Middle-Late Triassic of South America. The most recently erected proterochampsid species is ''Chanaresuchus ischigualastensis'', based on a single, fairly complete skeleton from the early Late Triassic Ischigualasto Formation of northwestern Argentina. We describe here in detail the non-braincase cranial and postcranial anatomy of this species and revisit its taxonomy and phylogenetic relationships. The phylogenetic analysis recovered 'Chanaresuchus ischigualastensis' as part of a trichotomy together with Gualosuchus reigi and Chanaresuchus bonapartei. Accordingly, ''Chanaresuchus ischigualastensis'' can be potentially more closely related to Gualosuchus reigi , or even Rhadinosuchus gracilis, than to Chanaresuchus bonapartei. In addition, after discussing previously claimed synapomorphies of Chanaresuchus, we could not find unambiguous support for the monophyly of the genus. As a result, we propose here the erection of the new genus Pseudochampsa for 'Chanaresuchus ischigualastensis', which results in the new combination Pseudochampsa ischigualastensis. The information provided here about the anatomy and taxonomy of Pseudochampsa ischiguaslastensis will be useful for future quantitative analyses focused on the biogeography and macroevolutionary history of proterochampsids. Copyright: